1989
DOI: 10.1073/pnas.86.7.2498
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic agonists and phorbol esters increase tyrosine phosphorylation of a 40-kilodalton protein in hippocampal slices.

Abstract: We have used the hippocampal slice preparation to investigate the regulation of protein tyrosine phosphorylation in brain. After pharmacological treatment ofintact slices, proteins were separated by electrophoresis, and levels of protein tyrosine phosphorylation were assessed by immunoblotting with specific anti-phosphotyrosine antibodies. Phorbol esters, activators of the serine-and threonine-phosphorylating enzyme protein kinase C, selectively increase tyrosine phosphorylation of a soluble protein with an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 43 publications
(34 reference statements)
0
33
0
1
Order By: Relevance
“…These include thrombin (22,30,46), collagen (50), and vasopressin (32) in platelets, fMetLeuPhe in neutrophils (39), muscarinic agonists in hippocampal slices (64), and phytohemagglutinin in Jurkat T cells (69). Disparate findings have been reported regarding the signaling pathways involved in this atypical tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 76%
“…These include thrombin (22,30,46), collagen (50), and vasopressin (32) in platelets, fMetLeuPhe in neutrophils (39), muscarinic agonists in hippocampal slices (64), and phytohemagglutinin in Jurkat T cells (69). Disparate findings have been reported regarding the signaling pathways involved in this atypical tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 76%
“…Recent studies reveal that the src family of tyrosine kinases can potentiate I NMDA and that this may be mediated by phosphorylation of tyrosine in the C-terminal domain of the NR2A subunit (51)(52)(53)(54). Interestingly, activation of muscarinic receptors can activate tyrosine kinases in hippocampal slices (60,61), suggesting that m1-induced activation of tyrosine kinase could mediate the m1-induced potentiation of I NMDA . However, future studies will be needed to rigorously test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…By modulating spontaneous synaptic activity in neuronal cultures with extracellular Ca 2+ and tetrodotoxin (TTX), Murphy et al (1994) observed that constitutive MAPK activity increased slowly (10 min to maximal levels) with synaptic stimulation and decreased gradually (20 min to return to baseline) after the addition of TTX. MAPK must be phosphorylated on tyrosine and threonine residues to become constitutively active, which is mediated by a PKC-regulated activator kinase (Stratton et al 1989). In contrast, CaMKII activation was rapid (10 sec) and decayed to baseline within 3 min after TTX treatment.…”
Section: Discussionmentioning
confidence: 99%